2020
DOI: 10.1111/nmo.13829
|View full text |Cite
|
Sign up to set email alerts
|

Normative values for gastric motility assessed with the 3D‐transit electromagnetic tracking system

Abstract: Background:The Motilis 3D-Transit system allows ambulatory description of transit patterns throughout the gastrointestinal tract and offers an alternative method for studying gastric motility. We aimed to establish normative values for gastric motility assessed with the method. Method:A total of 132 healthy volunteers ingested the 3D-Transit capsule for assessment of gastrointestinal transit times. Recordings from 125 subjects were used for definition of normative values. Forty-six subjects were studied on two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The 3D-Transit system can track three capsules simultaneously without interference, and the measures of transit times are found to be valid, reproducible, and comparable to transit times measured with radio-opaque markers [110]. Normative data on healthy subjects are available and comparable to normative data on transit times from the wireless motility capsule [100,113,114]. The main drawbacks of using this pan-enteric, diagnostic tool is the time-consuming and challenging data analysis, no CE-marking, and no availability outside research settings [112].…”
Section: Emerging Methods For Assessment Of Gastroenteropathy 41 Whole Gut Assessmentmentioning
confidence: 78%
“…The 3D-Transit system can track three capsules simultaneously without interference, and the measures of transit times are found to be valid, reproducible, and comparable to transit times measured with radio-opaque markers [110]. Normative data on healthy subjects are available and comparable to normative data on transit times from the wireless motility capsule [100,113,114]. The main drawbacks of using this pan-enteric, diagnostic tool is the time-consuming and challenging data analysis, no CE-marking, and no availability outside research settings [112].…”
Section: Emerging Methods For Assessment Of Gastroenteropathy 41 Whole Gut Assessmentmentioning
confidence: 78%
“…Additionally, the distal part is responsible for the breaking of solid foods by grinding, propelling, and mixing the undigested food with gastric secretions for enzymatic breakdown. In a recent study, Sutter, et al [ 12 ] reported that the rate of gastric contraction ranges between 2.6 and 3.8 times per minute, and the median contraction frequency is higher in women (3.2 times per minute) and lower in men (3.0 times per minute). Further, gastric secretion consists of hydrochloric acids, electrolyte salts, mucus, enzymes such as gastric lipase (digest fats) and pepsin (to digest protein), and various hormones.…”
Section: Overview Of Digestionmentioning
confidence: 99%
“…In healthy volunteer studies, use of the 3D-Transit capsule has provided normative values for regionspecific gastric, small intestinal, and segmental colonic GI transit times [52,55]. In volunteer and patient studies, the system has provided detailed information on colonic motility not available by any other ambulatory method [53,[56][57][58].…”
Section: Use Of 3d-transit In Researchmentioning
confidence: 99%
“…In volunteer and patient studies, the system has provided detailed information on colonic motility not available by any other ambulatory method [53,[56][57][58]. In clinical studies, the 3D-Transit system has been used to investigate transit times and movement patterns in patient groups including those with severe ulcerative colitis, Parkinson's disease, idiopathic gastroparesis, diabetes mellitus, and carcinoid diarrhea [55,57,[59][60][61].…”
Section: Use Of 3d-transit In Researchmentioning
confidence: 99%